Secret Guilt of an Artist: The Real Inspector Hound and Tom Stoppard’s Political Voice - Kevin Drzakowski ([sic])
Tom Stoppard once famously proclaimed his guilt that art is unimportant. The character Moon from Stoppard’s early farce The Real Inspector Hound presents surprising evidence that Stoppard’s view of art in his early years as a playwright may have been more complex than he let on. The circumstances behind Moon’s journey into the very art he criticizes are not unlike Tom Stoppard’s foray into politically conscious drama. Moon desperately wants the thriller he is reviewing to mean more than it really does. His wish becomes a reality when a third party, Puckeridge, forcibly pulls Moon into the fantasy. Like Moon, Stoppard had a fantasy, a dream-world in which art has the power to enact social change. Stoppard was unwilling or unable to act on that desire alone, until his own Puckeridge, an artist and dissident named Victor Fainberg, compelled him to act on his dream and merge art with politics.Keywords: Stoppard, The Real Inspector Hound, Fainberg, art, politics